Comic Strips in Teaching Simple Past Tense for EFL Learners - Al Faruq, Habibatul Azizah; Nurhalimah, Nurhalimah (ELLITE, 2018)
Teaching English needs various media and methods to make the studentsenthusiastic in teaching and learning process. A lot of media are employed inteaching and learning process. One of media used in teaching grammar especiallytenses is comic strips. Comic strips tell a story in form of pictures series and textstructures or dialogue. This article aims to find out the effect of using Englishcomic strips as media in teaching simple past tense. A quasi experimental designis used in this study to identify the causal impact of an intervention on targetpopulation without random assignment when the treatments were given. Thesubjects of this study were the seventh grade students of junior high school.The finding of t-test obtained was 3.865 which were higher than t-table 2.08.It means that the comic strips are effective for teaching simple past tense. Thecomic strips can be used in teaching other aspects such as storytelling, anothertense, writing and so forth, and also it can be collaborated with the students’learning style.